2020
DOI: 10.1002/ange.202007406
|View full text |Cite
|
Sign up to set email alerts
|

Induced Fitting and Polarization of a Bromine Molecule in an Electrophilic Inorganic Molecular Cavity and Its Bromination Reactivity

Abstract: Dodecavanadate, [V12O32]4− (V12), possesses a 4.4 Å cavity entrance, and the cavity shows unique electrophilicity. Owing to the high polarizability, Br2 was inserted into V12, inducing the inversion of one of the VO5 square pyramids to form [V12O32(Br2)]4− (V12(Br2)). The inserted Br2 molecule was polarized and showed a peak at 185 cm−1 in the IR spectrum. The reaction of V12(Br2) and toluene yielded bromination of toluene at the ring, showing the electrophilicity of the inserted Br2 molecule. Compound V12(Br2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…In the field of small‐molecule activation, Kikukawa et al. have recently broken new ground by using the bowl‐shaped dodecavanadate [V 12 O 32 ] 4− to bind elemental Br 2 in the central cavity, thereby leading to polarization of the Br−Br bond and significant selectivity changes in organic bromination reactions [131] . In a related example, Das and co‐workers demonstrated that POVs can sequester CO 2 from air and store it as an internal CO 3 2− template, thereby resulting in the species [H 8 V IV 15 O 36 (CO 3 )] 6− [132] .…”
Section: Outlook and Emerging Topicsmentioning
confidence: 99%
“…In the field of small‐molecule activation, Kikukawa et al. have recently broken new ground by using the bowl‐shaped dodecavanadate [V 12 O 32 ] 4− to bind elemental Br 2 in the central cavity, thereby leading to polarization of the Br−Br bond and significant selectivity changes in organic bromination reactions [131] . In a related example, Das and co‐workers demonstrated that POVs can sequester CO 2 from air and store it as an internal CO 3 2− template, thereby resulting in the species [H 8 V IV 15 O 36 (CO 3 )] 6− [132] .…”
Section: Outlook and Emerging Topicsmentioning
confidence: 99%
“…Auf dem Gebiet der Aktivierung kleiner Moleküle haben Kikukawa und Kollegen kürzlich neue Wege beschritten, indem sie das schalenförmige Dodekavanadat [V 12 O 32 ] 4− verwendeten, um elementares Br 2 im zentralen Hohlraum zu binden, was zu einer Br‐Br‐Bindungspolarisation und signifikanten Selektivitätsänderungen in organischen Bromierungsreaktionen führt [131] . In einem verwandten Beispiel zeigten Das und Mitarbeiter, dass POVs CO 2 aus der Luft sequestrieren und als internes CO 3 2− ‐Templat speichern können, was zu der Spezies [H 8 V IV 15 O 36 (CO 3 )] 6− führte [132] .…”
Section: Ausblick Und Neue Themenunclassified